Dizziness in postural tachycardia syndrome and its link to vestibular migraine - Sekhon, Ruby; Gall, Nicholas; Ainsworth, Carolyn; Murdin, Louisa (Frontiers in Neurology, 2025)
BackgroundPostural tachycardia syndrome (PoTS) is a chronic condition characterized by an increased heart rate upon standing and is recognized to be associated with dizziness and migraines. This study aimed to investigate the multifaceted nature of dizziness in PoTS from a vestibular perspective, including the relationship with vestibular migraine.MethodsA retrospective review of 80 patients with confirmed PoTS, attending a tertiary neuro-otology clinic, was conducted to evaluate standardized detailed assessments validated symptom questionnaires, history/physical examination, neuro-otological diagnostics [including video head impulse test (VHIT), videonystagmography (VNG), and caloric testing], and management. The PoTS cohort was also compared with an age- and sex-matched control group of dizzy patients.ResultsA total of 80 patients were included (mean age: 35.3 years ± 12.1; 93% women). Approximately 84% had migraine, and 30% had vestibular migraine. Clinical examination of static and dynamic balance was most frequently abnormal. VHIT was abnormal in 2%, and VNG canal paresis and directional preponderance were abnormal in 19 and 22%, respectively. In total, 49% of cases were offered migraine management advice, and 58% were offered vestibular rehabilitation. The PoTS group showed higher rates of vestibular symptoms, including vertigo, unsteadiness, and positional vertigo, and high Disability Rating Scale (DRS) scores.ConclusionOur findings reflect the challenges of distinguishing dizziness phenotypes in PoTS, particularly vestibular migraine. This study illustrates the importance of judicious clinical enquiry to investigate non-orthostatic dizziness mechanisms, such as vestibular migraine, for which evidence-based management exists, and recommends further research to elucidate the multifaceted nature of PoTS-associated dizziness.